PERTUMBUHAN DAN PRODUKSI BEBERAPA VARIETAS PADI (Oryza sativa L) PADA BERBAGAI TINGKAT SALINITAS - Muhammad Jalil; Halimatun Sakdiah; Eka Deviana; Ilham Akbar (Universitas Teuku Umar, 2018)
This study aims to determine the effect of salinity on growth and production of some varieties of rice as well as real whether the interaction of both factors. This research used a randomized block design (RBD) factorial design with three replications. The first factor consists of 5 levels: varieties IR-64, Ciherang, Inpari 11 IRBB-27 and Inpara. The second factor consists of three levels: salinity levels of 0 ppm/l (control), 2000 ppm/l and 4000 ppm/l. This research was conducted at the experimental field of Agriculture Faculty on Teuku Umar University from January 22 to 28 June 2015. The results showed that the salinity gave significant effect on the number of grains per panicle. Significant number of panicle, grain weight per panicle and production per hectare and not influenced on other treatments. Varieties gave significant effect on plant height and number of tillers age on 30 day after plant, age 45 day after plant, leaf length, number of productive panicles, panicle length, number of grains per panicle, percentage of empty grain, the percentage of pithy grain, grain weight per panicle and yield per hectare. Significant effect on plant height age 45 day after plant, age 15 day after plantntiller number and weight of 100 grains and not influenced on other treatments. There is a very real interaction between salinity and varieties of the grain hollow percentage, percentage pithy grain, grain weight per panicle and yield per hectare, significantly affected the number of grains per panicle and no significant effect on other variables. Keywords: marginal land, salinity, tidal land, varieties